Difluorobenzothiadiazole based two-dimensional conjugated polymers with triphenylamine substituted moieties as pendants for bulk heterojunction solar cells - W. H. Lee; B. T. Liu; R. H. Lee (eXPRESS Polymer Letters)
Three donor/acceptor (D/A)-type two-dimensional polythiophenes (PTs; PBTFA13, PBTFA12, PBTFA11) featuring difluorobenzothiadiazole (DFBT) derivatives as the conjugated (acceptor) units in the polymer backbone and tertbutyl–substituted triphenylamine (tTPA)-containing moieties as (donor) pendants have been synthesized and characterized. These PTs exhibited good thermal stabilities, broad absorption spectra, and narrow optical band gaps. The cutoff wavelength of the UV–Vis absorption band was red-shifted upon increasing the content of the DFBT units in the PTs. Bulk heterojunction solar cells having an active layer comprising blends of the PTs and fullerene derivatives [6,6] phenyl-C61/71-butyric acid methyl ester (PC61BM/PC71BM) were fabricated; their photovoltaic performance was strongly dependent on the content of the DFBT derivative in the PT. Incorporating a suitable content of the DFBT derivative in the polymer backbone enhanced the solar absorption ability and conjugation length of the PTs. The photovoltaic properties of the PBTFA13-based solar cells were superior to those of the PBTFA11- and PBTFA12-based solar cells.